Foxp3-Positive Regulatory T Cells Contribute to Antifibrotic Effects in Renal Fibrosis via an Interleukin-18 Receptor Signaling Pathway - Hirooka, Yasuaki; Nozaki, Yuji; Niki, Kaoru; Inoue, Asuka; Sugiyama, Masafumi; Kinoshita, Koji; Funauchi, Masanori; Matsumura, Itaru (Frontiers in Medicine, 2020)
Renal interstitial fibrosis is a common lesion in the process of various progressive renal diseases. Interleukin (IL)-18 is a proinflammatory cytokine that plays an important role in the induction of Th1 responses and is associated with renal interstitial fibrosis, but the mechanism of fibrosis remains unclear. Here we used IL-18 receptor alpha knockout (IL-18Rα KO) mice to investigate the role of an IL-18Rα signaling pathway in renal fibrosis in a murine model of unilateral ureteral obstruction. IL-18 Rα KO mice showed decreased renal interstitial fibrosis and increased infiltration of CD4+ T cells and Foxp3+ regulatory T cells (Tregs) compared to the wildtype (WT) mice. The renal mRNA expression of transforming growth factor beta 1 (TGF-β1, which is considered an important cytokine in renal interstitial fibrosis) was not significantly different between the WT and IL-18Rα KO mice. The adoptive transfer of CD4+ T cells from the splenocytes of IL-18Rα KO mice to WT mice reduced renal interstitial fibrosis and increased the number of Foxp3+ Tregs in the WT mice. These results demonstrated that Foxp3+ Tregs have a protective effect in renal interstitial fibrosis via an IL-18R signaling pathway.